Una vita irrazionale - Vari, Autori (Il sogno della farfalla, 2007)
Roma, The small and medium-sized publisher’s book fair “Più libri più liberi” (more books, more freedom). On the 8th December 2006, Massimo Fagioli’s latest book was presented in Rome. It brings together the lessons he held at the Università of Chieti in 2006. The papers delivered on the day highlighted the evolution of his writing and language, from the early 70s, through to his experience with the Collective Analysis and the latest publications which re-propose to a wider readership the author’s theories and research, and their application within a contemporary scientific, cultural and political context. During the debate Fagioli placed great emphasis on the importance of his research into non-conscious images, based on his rejection of the identification between the irrational and mental illness. The emergence of a non-violent relationship with an individual “different” from oneself, starting from the male-female relationship, is made possible.